A prospective study of effects of prenatal maternal stress on later eating‐disorder manifestations in affected offspring: Preliminary indications based on the project ice storm cohort. Issue 5 (23rd March 2015) - St‐Hilaire, Annie; Steiger, Howard; Liu, Aihua; Laplante, David P.; Thaler, Lea; Magill, Tara; King, Suzanne
ABSTRACT Background Research associates maternal stress exposures (especially when occurring late in gestation) with heightened risk of subsequent emotional and behavioral problems in affected offspring. However, as yet, no study has examined the association between prenatal maternal stress (PNMS) and affected children's risk of anorexia‐ or bulimia‐type eating disturbances. Objective To study the influences of PNMS on later disordered eating in exposed offspring. Method We used the Eating Attitudes Test (EAT)‐26 to measure eating attitudes and behaviors in 54 thirteen‐year olds whose mothers had been exposed, while pregnant with these children, to the 1998 Quebec Ice Storm—a natural disaster regarded as a model of exposure to severe environmental stress. Mothers' stress was measured shortly after exposure to the storm using established indices of objective and subjective stress. Results Hierarchical multiple linear regression analyses indicated that once variance owing to children's body mass index and sex was accounted for, stress exposures during the third trimester of pregnancy predicted elevated EAT‐26 scores in affected children—perhaps even more so when levels of objective stress were high. Discussion Third trimester exposure to PNMS, especially when objectively severe, seems to be associated with increased eating‐disorder‐linked manifestations in affected early adolescents. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:512–516)